Applying Flipped Learning Strategy to Develop EFL Students' Reading Comprehension Skills at the Faculty of Specific Education - Mahmoud, Neveen Hassan; Mohamed, Fatima Sadek; Abdel Wahab, Amr Fathy (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of the present study is to investigate the effect of applying a flipped learning strategy on developing reading comprehension skills among sophomores at the Faculty of Specific Education. The study adopted the one-group design, in which 30 students participated from second year, English section at the Faculty of Specific Education, Zagazig University during the academic year 2019/2020. They were instructed by applying the flipped learning strategy. To obtain data, two instruments were used: a pre-post reading comprehension skills test.Findings showed that the flipped learning strategy improved students' reading comprehension skills. Thus, it is recommended to utilize flipped learning as a new strategy in developing EFL students' reading comprehension skills.